14-3-3 Dysfunction in Dorsal Hippocampus CA1 (dCA1) Induces Psychomotor Behavior via a dCA1-Lateral Septum-Ventral Tegmental Area Pathway - Zhang, Jiajing; Navarrete, Meaghan; Wu, Yuying; Zhou, Yi (Frontiers in Molecular Neuroscience, 2022)
While hippocampal hyperactivity is implicated in psychosis by both human and animal studies, whether it induces a hyperdopaminergic state and the underlying neural circuitry remains elusive. Previous studies established that region-specific inhibition of 14-3-3 proteins in the dorsal hippocampus CA1 (dCA1) induces schizophrenia-like behaviors in mice, including a novelty-induced locomotor hyperactivity. In this study, we showed that 14-3-3 dysfunction in the dCA1 over-activates ventral tegmental area (VTA) dopaminergic neurons, and such over-activation is necessary for eliciting psychomotor behavior in mice. We demonstrated that such hippocampal dysregulation of the VTA during psychomotor behavior is dependent on an over-activation of the lateral septum (LS), given that inhibition of the LS attenuates over-activation of dopaminergic neurons and psychomotor behavior induced by 14-3-3 inhibition in the dCA1. Moreover, 14-3-3 inhibition-induced neuronal activations within the dCA1-LS-VTA pathway and psychomotor behavior can be reproduced by direct chemogenetic activation of LS-projecting dCA1 neurons. Collectively, these results suggest that 14-3-3 dysfunction in the dCA1 results in hippocampal hyperactivation which leads to psychomotor behavior via a dCA1-LS-VTA pathway.